Draft Fourth Five Year Plan of Andaman and Nicobar Islands 1966-71 - Planning Commission (Planning Commission, 1966)
Draft of the Fourth Five Year Plan has. been prepared keeping in view the tentative outlay of Rs. 11 crores fixed by the Planning Commission in accordance with the instructions contained in their letter No.PC(P)l(4)l/UT/66 dated the 22nd September, 1966. The estimated outlay of the proposals as included in the Draft Fourth Five Year Plan works out to Rs.11.956 crores. The Draft includes a short memorandum on the Fourth Plan proposals and brief notes on individual heads of development.
Andaman and Nicobar Islands